El acceso a la justicia de las poblaciones indígenas. Una necesidad desde el lenguaje - Hurtado, Giovana (2024)
Indigenous populations face limitations in understanding the justice system due to linguistic and cultural barriers; therefore, the use of clear and accessible language is essential for them to be able to exercise their rights and participate effectively in judicial processes. Through a documentary review of the problems faced by indigenous populations in accessing justice, the strategies developed by the Peruvian Judiciary are described. It is stated that, despite the existence of regulations and policies that guarantee access to translators and interpreters in the judicial sphere, actions are limited and need to be strengthened. Strategies that remain in place over time are required, and that allow their impact to be measured in order to evaluate their relevance and effectiveness. It concludes that there is a need to develop a linguistic policy focused on justice, which includes incentives - in the training of lawyers from indigenous populations - as a mechanism for preserving indigenous languages. Likewise, the importance of carrying out linguistic planning in the administration of justice is highlighted in order to have operators who speak indigenous languages ​​in each judicial district, specialty and instance.